Anthropological investigations in Dakhleh Oasis, Egypt i in 1977 - Dzierżykray-Rogalski, Tadeusz (Anthropological Review, 1978)
Author presents his anthropological works conducted in a frame of Expedition of LF.A.O. (French Institute of Oriental Archacology) in on of the least accessible oasis in the Lybian Desert. Examination of bone materials was undertaken in the neighbourhood of Ain Aseel city and Qila el Dubbeh necropolis of VI Dynasty. — In first season of work author examined bone remains from Ptolemaic period discovered in old Mastaba M II CD. It was possible to distinguish 71 individuals, all of them were measured at the spot. In his report author presents preliminary demographical data (table I), he estimates the mean age at death of males at 53.4 years, the mean for female at 43.1 years. These means are high what might be related to high standard of living in this group, but it can not be generalized for the whole population of the Oasis. Apart from demographical data and measurements author has done interesting paleopathological observations which will be presented in detailed elaboration of the material.